On the stability of the quadratic mapping in normed spaces - Gwang Hui Kim (International Journal of Mathematics and Mathematical Sciences)
The Hyers-Ulam stability, the Hyers-Ulam-Rassias stability, and also the stability in the spirit of Gavruţa for each of the following quadratic functional equations f(x+y)+f(x−y)=2f(x)+2f(y), f(x+y+z)+f(x−y)+f(y−z)+f(z−x)=3f(x)+3f(y)+3f(z), f(x+y+z)+f(x)+f(y)+f(z)=f(x+y)+f(y+z)+f(z+x) are investigated.